1988
DOI: 10.1042/bj2560515
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glucose carrier activity by AlCl3 and phospholipase C in fat-cells

Abstract: (1) the data show that AlCl3, probably through activation of a pertussis-toxin-inhibitable G protein, and PLC are able to modulate the intrinsic glucose carrier activity; (2) as pertussis toxin did not modify the effect of insulin, it seems unlikely that the insulin signal on glucose transport involves activation of this specific G protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
1
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 29 publications
5
27
1
1
Order By: Relevance
“…PAF-stimulated GLUT4 Translocation-GTP␥S or NaF plus AlCl 3 treatments triggered the GLUT4myc translocation in both 3T3-L1-GLUT4myc adipocytes and CHO-GLUT4myc cells, as did the endogenous GLUT4 translocation in 3T3-L1-adipocytes (6,13,14,23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAF-stimulated GLUT4 Translocation-GTP␥S or NaF plus AlCl 3 treatments triggered the GLUT4myc translocation in both 3T3-L1-GLUT4myc adipocytes and CHO-GLUT4myc cells, as did the endogenous GLUT4 translocation in 3T3-L1-adipocytes (6,13,14,23).…”
Section: Resultsmentioning
confidence: 99%
“…However, we reported that the small GTP-binding proteins, Ras, Rab3D, Rad, and Rho are unlikely to be involved in the GLUT4 translocations with insulin, phorbol 12-myristate 13-acetate (PMA), and GTP␥S treatments, and that the signaling pathway of the GTP␥S-stimulated GLUT4 translocation is different from those of insulin and PMA treatments (22). In addition, NaF plus AlCl 3 treatment, which is known to activate heterotrimeric GTP-binding proteins, stimulates GLUT4 translocation and glucose uptake in adipocytes and in CHO cells (6,23). This suggests that heterotrimeric GTP-binding protein(s) may be involved in the GTP␥S-stimulated GLUT4 translocation.…”
mentioning
confidence: 99%
“…In the past few years evidence has accumulated which suggests that insulin receptor signalling may involve coupling to GTP-binding proteins [1][2][3][4][5][6][7]. This view is mainly supported by the effects of cholera and pertussis toxin on insulin action.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GTP␥S can stimulate GLUT4 translocation in the absence of ATP, suggesting that ATP is required at an early step(s) in the insulin-signaling pathway and that a GTP-binding protein(s) functions at a more distal step(s) (11). The stimulatory effect of GTP␥S can also be mimicked by treatment with AlF 4 Ϫ , which is characteristic of the involvement of a heterotrimeric GTP binding protein (12,13). Consistent with this interpretation, adrenergic stimulation can induce GLUT4 translocation and glucose uptake in both cardiac myocytes (14,15) and brown adipocytes (16,17).…”
mentioning
confidence: 98%